Genotype–Phenotype Correlation in Progressive Supranuclear Palsy Syndromes: Clinical and Radiological Similarities and Specificities - Ruiz-Barrio, Iñigo; Horta-Barba, Andrea; Illán-Gala, Ignacio; Kulisevsky, Jaime; Pagonabarraga, Javier (Frontiers in Neurology, 2022)
The progressive supranuclear palsy (PSP) syndrome encompasses different entities. PSP disease of sporadic origin is the most frequent presentation, but different genetic mutations can lead either to monogenic variants of PSP disease, or to other conditions with different pathophysiology that eventually may result in PSP phenotype. PSP syndrome of monogenic origin is poorly understood due to the low prevalence and variable expressivity of some mutations. Through this review we describe how early age of onset, family history of early dementia, parkinsonism, dystonia, or motor neuron disease among other clinical features, as well as some neuroimaging signatures may be important clues to suspect PSP syndrome of monogenic origin. In addition, a diagnostic algorithm is proposed that may be useful to guide the genetic diagnosis once there is clinical suspicion of a monogenic PSP syndrome.